Correlation The Number Of Erythrocytes And Glucose Level From Serum Which 2 Hours Delayed From Delayed - Bastian Darwin; Eka Yuniar; Endang Endang; Ian Kurniawan (Poltekkes Kemenkes Mataram, 2020)
In the processing of specimens, serum specifically should be separated from blood cell the process of glucose glycolysis which caused decreasing levels of glucose. The very high number of erythrocyte can cause a glycolysis, so the decreasing of the levels of glucose will be happen. This study was pre-experiment using One Group Pretest Posttest. The sample was taken using purposive sampling technique and there were 30 subjects. The sample was EDTA bloods and serum which had been treated such as Separation of Glucose Serum which was 2 hours delayed and Separation of Glucose Serum which was checked directly. From this study we can found that the average of the glucose levels on serum separation which is 2 hours delayed was 91 mg/dL and the Separation of Glucose Serum which is checked directly was 97mg/dL. Based on paired T test the result, the data showed that there were differences from average levels of glucose between serum which was checked directly and separation of Serum which was 2 hours delayed. The average from the number of erythrocyte was 5,0 million/µL. Based on pearson correlation, there was no correlation between the number of erythrocyte and glucose level on serum separation which is 2 hours delayed.